Digital Transformation in Indonesian FDA (Food and Drug Authority) - Anggia Saniagati; John Welly (Journal of International Conference Proceedings, 2021)
The Indonesian Food and Drug Authority (FDA) or BPOM has an essential role in enhancing domestic pharmaceutical, traditional medicine, health supplements, cosmetics, and food industry competitiveness. The Indonesian FDA has implemented drug and food supervision to accelerate the achievement of SDG 16: build effective, accountable, and inclusive institutions at all levels by taking advantage of emerging technological developments to innovate public services. Digital transformation is key to accelerating SDGs in customer experience, operations, employee experience, business model, and digital platform. This study aimed to assess the digital maturity of the Indonesian FDA and provide the business solution on how the Indonesian FDA goes digital into a smart government. The results are expected to assist the organization in analyzing, properly structuring, and understanding the nature of the problem to be addressed, facilitating the creation of short and long-term goals and plans, providing a foundation to assist organizations in assessing realistically where they are in their transformation journey, and making investments in transformation projects more effective. The business solution is also expected to support and give insightful thoughts in digital innovation and acceleration to achieve Indonesia's Digital Transformation.